2021
DOI: 10.3390/ijerph18020637
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Health Risk Factors in Vocational Education Students: A Systematic Review

Abstract: Health risk factors such as tobacco smoking, inadequate fruit intake, inadequate vegetable intake, risky alcohol consumption, physical inactivity, obesity, anxiety and depression often commence during adolescence and young adulthood. Vocational education institutions enrol many students in these age groups making them an important setting for addressing multiple health risk factors. This systematic review examined (i) co-occurrence of health risk factors, (ii) clustering of health risk factors, and (iii) socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…These two groups both had a higher likelihood of mortality than Class 3 (nondrinker, nonsmoker, more dietary intake, and active), where people engaged in PA and had a high intake of fruits and vegetables. This is consistent with the results from studies carried out in other countries, including the USA [42], where physical inactivity and low fruit and vegetable intake were found the most predominant co-occurring behaviors, although the clustering investigation varied based on the target population [30]. A review by Meader and colleagues indicated that co-occurrence data showed a particularly high prevalence for low fruit and vegetable intake and low PA, which was consistent with our findings [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These two groups both had a higher likelihood of mortality than Class 3 (nondrinker, nonsmoker, more dietary intake, and active), where people engaged in PA and had a high intake of fruits and vegetables. This is consistent with the results from studies carried out in other countries, including the USA [42], where physical inactivity and low fruit and vegetable intake were found the most predominant co-occurring behaviors, although the clustering investigation varied based on the target population [30]. A review by Meader and colleagues indicated that co-occurrence data showed a particularly high prevalence for low fruit and vegetable intake and low PA, which was consistent with our findings [31].…”
Section: Discussionsupporting
confidence: 92%
“…However, another study found that males and those with greater social disadvantages engaged in riskier healthbehaviors [32]. The present study showed that women belonged to the class 1 having the lowest prevalence of alcohol consumption but were highly physically inactive, whereas a study by Atorkey et al found that women were less likely to engage in hazardous drinking and tobacco smoking but were more likely to engage in hazardous drinking and physical inactivity [30]. Some research points out several possible explanations for this gender effect.…”
Section: Discussioncontrasting
confidence: 58%
“…These results are consistent with those of the previous studies that have confirmed a significant difference in health behaviors according to the high school system [ 30 , 31 ]. According to Atorkey et al’s [ 32 ] systematic review, as vocational high school students become more independent during vocational education training and tend to choose their own lifestyle habits, they have an increased risk of engaging in unhealthy behaviors such as smoking, eating fast food, and physical inactivity. Since the risk factors affecting these health behaviors appear complex, a comprehensive and preventive intervention strategy should be developed and delivered in the school environment to promote the health of vocational high school students.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has reported that a substantial proportion of vocational education students engage in multiple health risk behaviours such as smoking tobacco, poor nutrition (i.e., inadequate fruit and vegetable intake), alcohol use, and physical inactivity (SNAP), highlighting the importance of understanding uptake of support services to modify these behaviours in this population [27]. Vocational education students study courses such as carpentry, floristry, plumbing, automotive engineering, hairdressing, and commercial cooking at vocational education institutions such as trade schools, technical schools, community colleges, and colleges of further education [28].…”
Section: Introductionmentioning
confidence: 99%